Genetic testing in individuals with extreme HDL-C levels: Diagnostic yield and clinical implications from the Tromsø Study - Åsa Schawlann Ølnes; Marianne Teigen; Thea Bismo Strøm; Erik Kristoffer Arnesen; Antoine Rimbert; Anne Elise Eggen; Katrine Bjune (PLoS ONE, 2026)
Aim This study aimed to assess the prevalence of genetic variants responsible for extreme levels of high-density lipoprotein cholesterol (HDL-C) and evaluate the adequacy of current thresholds for genetic testing of HDL-related dyslipidemia. Methods Using data from the Tromsø Study, a population-based cohort in Northern Norway, we identified 210 individuals with HDL-C levels ≤ 0.5 mmol/L or ≥ 3.0 mmol/L. Six HDL-related genes ( ABCA1, APOA1, CETP, LCAT, PLTP, SCARB1 ) were sequenced in these participants. We classified variants according to ACMG guidelines, incorporating functional assays and UK Biobank data for additional phenotype-genotype associations. Results We identified 38 variants of interest across six HDL-related genes, of which 10 were considered potentially causative, found in 14 individuals. Genetic causes were detected in 33.3% of individuals with low HDL-C and 5.05% of those with high HDL-C. Sex-specific analyses showed that using HDL-C thresholds aligned with population distributions improved detection of individuals with pathogenic variants, particularly among women with high HDL-C and men with low HDL-C. These findings suggest that current uniform thresholds may overlook clinically relevant cases and that incorporating sex-specific HDL-C distributions could enhance the identification of individuals with suspected genetic HDL disorders. Conclusions Genetic testing for HDL-related dyslipidemia is underutilized, with many individuals not meeting the current extreme HDL-C threshold criteria. Revised sex-specific thresholds for genetic testing will improve the identification of pathogenic variants and provide more accurate diagnoses of HDL-related disorders. Continued research is essential to refine our understanding of HDL genetics and its clinical implications.